The Lelang Kue Tradition at Kuang Dalam Community Wedding - Aravik, Havis; Ahmad Tohir (Jurnal Studi Islam Indonesia (JSII), 2025)
This research aims to uncover the social and cultural meanings of the Lelang Kue tradition, using the field study method as the main approach. This tradition is not simply part of the procession leading up to a wedding, but rather reflects a custom-based socio-economic system that binds the community together through the values of mutual aid, social solidarity and collective responsibility. The Lelang Kue serves as a means of raising funds for customary needs as well as strengthening social relations between neighbours. The active role of village girls as cake carriers also serves as a medium for passing on cultural values to the younger generation. This research uses a descriptive qualitative approach with a case study design. In practice, the bidding process in the auction involves all levels of society, reflecting respect, social commitment and status in the community. Based on Marcel Mauss' theory of giving, this activity contains the principle of reciprocity that strengthens social cohesion and moral obligations between individuals. The study results show that Lelang Kues play an important role in emphasising collective identity and maintaining local cultural heritage. This tradition is a clear example of how the Kuang Dalam community integrates economic, social and symbolic dimensions in their daily live